Desempenho econômico e financeiro das empresas distribuidoras de energia elétrica: um estudo nas companhias de capital aberto, sediadas no estado de São Paulo - Oliveira, Gilberto de Souza (2009)
This thesis begins with a systematic analysis of the electrical sector in Brazil and the main risks inherent to such sector. Then, it discusses certain information of the five largest publicly-held electric power distribution companies, based in the State of São Paulo, namely: Bandeirante Energia S.A.; Companhia Paulista de Força e Luz.; Companhia Piratininga de Força e Luz.; Elektro Eletricidade e Serviços S.A.; Eletropaulo Metropolitana Eletricidade de São Paulo S.A. It presents all the mandatory disclosure of financial statements under the Brazilian corporate law, as well as those required by the Granting Authority ANEEL, subsequently it presents a collection of indicators for analysis of financial statements, as well as the calculation methodology and interpretation and, finally, it presents a selection of indicators used in the study of five companies. The study is aimed to evaluate the economic and financial performance of these companies during the period from 2000 to 2007, focusing on two distinct stages: (i) the rationing of electricity period that lasted from June 2001 to February 2002, which had a huge impact on the financial statements for such periods, and (ii) the post rationing period, which was impacted by new standards established by the Federal Government in connection with the creation of a new model for the Brazilian energy sector, during the years 2004 and 2005. This thesis uses the evolutionary analysis, which evaluates the development of indicators for each of the five companies, checking the performance of their economic situation, financial performance, profitability and allocation of cash generated and consumed between two thousand and two thousand and seven